The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1124/jpet.103.060582
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Peripheral Morphine Analgesia Contributes to the Reduced Effectiveness of Systemic Morphine in Neuropathic Pain

Abstract: It is well known that the analgesic potency of morphine is reduced in neuropathic pain. In this study, we demonstrate that the decreased effectiveness of systemic morphine in neuropathic pain might be caused by the loss of morphine analgesia at the periphery. When given s.c. or i.t., the dose-response curves for morphine analgesia in Hargreaves thermal test were shifted rightward in partial sciatic nerve-injured mice compared with control sham-operated mice. The dose-response curves for i.c.v. morphine analges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
74
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 35 publications
18
74
1
Order By: Relevance
“…S8 A and B). Indeed, after peripheral nerve lesions, there is a consistent reduction in opioid-receptor expression in primary nociceptive neurons (28). Recently, it was shown that during neuropathic states, there is a reduction of K ATP currents in rat primary sensitive neurons, probably by a defect in upmodulation of these currents by NO and the Ca 2+ /Calmodulin/ CAMKII pathway (24,29).…”
Section: Cfa-induced Hypernociceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…S8 A and B). Indeed, after peripheral nerve lesions, there is a consistent reduction in opioid-receptor expression in primary nociceptive neurons (28). Recently, it was shown that during neuropathic states, there is a reduction of K ATP currents in rat primary sensitive neurons, probably by a defect in upmodulation of these currents by NO and the Ca 2+ /Calmodulin/ CAMKII pathway (24,29).…”
Section: Cfa-induced Hypernociceptionmentioning
confidence: 99%
“…This mechanism could not be immediately extended to neuropathic pain, because the peripheral analgesic effectiveness of morphine is greatly abrogated during neuropathic pain states (28) (Fig. S8 A and B).…”
Section: Cfa-induced Hypernociceptionmentioning
confidence: 99%
“…MORs expressed at primary sensory neurons and their central terminals in the spinal dorsal horn are essential for the analgesic effects of opioids (8 -10). Peripheral nerve injury reduces the expression level of MORs in the dorsal root ganglion (DRG), contributing to the loss of opioid analgesic efficacy in neuropathic pain (6,11,12). However, the epigenetic mechanisms by which nerve injury leads to diminished MOR expression in the DRG remain unclear.…”
mentioning
confidence: 99%
“…In patients with neuropathic pain, however, the analgesic potency of MOR agonists is reduced (3,4). The opioid effects are also diminished in animal models of neuropathic pain (5)(6)(7). MORs expressed at primary sensory neurons and their central terminals in the spinal dorsal horn are essential for the analgesic effects of opioids (8 -10).…”
mentioning
confidence: 99%
“…The lack of efficacy of opioids under neuropathic conditions has been previously shown and attributed to receptor down-regulation both centrally and peripherally (8), while such changes have not been observed during inflammation. In this issue of Arthritis & Rheumatism, Li and colleagues (9) report on a novel finding in an experimental rat model of chronic monarthritis.…”
mentioning
confidence: 84%